2005
DOI: 10.1542/peds.2004-1680
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Red Blood Cell Transfusions Among Preterm Infants: Results of a Randomized Trial With an In-Line Blood Gas and Chemistry Monitor

Abstract: As long as an umbilical artery catheter is available for blood sampling with an in-line blood gas and chemistry monitor, significant reductions in neonatal RBC transfusions can be achieved. The patients most likely to benefit from monitor use are the smallest, most critically ill newborns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
133
1
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(147 citation statements)
references
References 20 publications
4
133
1
5
Order By: Relevance
“…A retrospective review following the introduction of bedside point-of-care testing decreased transfusions by 43% without a change in the number of tests done [34]. A randomized controlled trial which decreased phlebotomy losses by 25% in the 1st week of life through the use of in-line blood gas and chemistry monitoring led to a 33% decrease in RBC transfusions [35]. …”
Section: Rbc Transfusionmentioning
confidence: 99%
“…A retrospective review following the introduction of bedside point-of-care testing decreased transfusions by 43% without a change in the number of tests done [34]. A randomized controlled trial which decreased phlebotomy losses by 25% in the 1st week of life through the use of in-line blood gas and chemistry monitoring led to a 33% decrease in RBC transfusions [35]. …”
Section: Rbc Transfusionmentioning
confidence: 99%
“…The anemia of prematurity occurs in all very low birth weight (VLBW) premature infants (birth weight Ͻ1500 g) and is exacerbated by iatrogenic blood loss resulting from frequent laboratory blood sampling for managing clinical illness (Strauss, 1995;Lin et al, 2000;Madan et al, 2005;Widness et al, 2005). The resulting development of clinically significant anemia is managed by the administration of red blood cell (RBC) transfusions, creating dynamic changes in the Hb mass in these infants due to both the physical removal and administration of erythrocytes.…”
mentioning
confidence: 99%
“…This is largely due to the complications in determining the erythropoiesis rate caused by frequent phlebotomies and RBC transfusions altering the RBC/Hb mass, and the effect of each phlebotomy on the RBC/Hb removal rate due to the life span-based disposition of RBCs (Landaw, 1988;Freise et al, 2007Freise et al, , 2008. Previous studies have demonstrated that on average 33.8 ml/kg blood is removed and 27.0 ml/kg blood is transfused during the first 4 weeks of life in infants born at a gestational age of less than 28 weeks (Madsen et al, 2000), and other studies have reported even higher phlebotomy blood loss volumes in the first 2 weeks of life alone (Lin et al, 2000;Widness et al, 2005). Thus, the effects of the physical removal and administration of RBCs are substantial and cannot be ignored.…”
mentioning
confidence: 99%
“…Moreover, although the number of transfusions has decreased over the past 20 years, extremely low birth weight (ELBW) infants are still receiving 3 to 5 PRBC transfusions per hospitalization, and are being exposed to 2 to 3 donors. 24,25 The success of this study compared with previous studies may be in part because of differences in study design. We compared early Darbe administration and the usual erythropoietic dose of Epo with placebo to determine if ESAs could decrease or prevent transfusions.…”
Section: Figurementioning
confidence: 94%